2020
DOI: 10.1111/jcmm.15909
|View full text |Cite
|
Sign up to set email alerts
|

Eva‐1 homolog A promotes papillary thyroid cancer progression and epithelial‐mesenchymal transition via the Hippo signalling pathway

Abstract: Recently, the incidence of thyroid cancer is increasing worldwide. Papillary thyroid cancer (PTC) is the most common histological type of thyroid cancer. Whole‐transcriptome sequence analysis was performed to further understand the primary molecular mechanisms of the occurrence and progression of PTC. Results showed that Eva‐1 homolog A (EVA1A) may be a potential gene for the PTC‐associated gene in thyroid cancer. In this work, the role of EVA1A expression in thyroid cancer was investigated. Real‐time PCR was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…In humans, the EVA1 family includes three main groups: EVA1A, EVA1B, and EVA1C. Previous studies have revealed that EVA1A, an endoplasmic reticulum-related protein were involved in regulating autophagy and apoptosis-related mechanisms in many cancers (11,12). Additionally, Bang-Yi Lin et al found that EVA1A promotes papillary thyroid cancer progression and epithelial-mesenchymal transition via upregulating immunerelated signaling pathways (11).…”
Section: Introductionmentioning
confidence: 99%
“…In humans, the EVA1 family includes three main groups: EVA1A, EVA1B, and EVA1C. Previous studies have revealed that EVA1A, an endoplasmic reticulum-related protein were involved in regulating autophagy and apoptosis-related mechanisms in many cancers (11,12). Additionally, Bang-Yi Lin et al found that EVA1A promotes papillary thyroid cancer progression and epithelial-mesenchymal transition via upregulating immunerelated signaling pathways (11).…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure 5A , MAPK8IP1P2 overexpression was positively correlated with activity of Hippo signaling pathway, but negatively associated with the transcriptional activity of downstream co-activators YAP1/TAZ of Hippo signaling. Inactivation of Hippo signaling has been widely reported to be implicated in anoikis resistance and metastatic thyroid cancer ( 9 , 50 , 51 ), as well as in lymphatic metastasis process of cancers ( 52 , 53 ), suggesting that Hippo signaling may mediate the functional role of MAPK8IP1P2 in lymphatic metastasis of thyroid cancer. Luciferase reporter assay showed that upregulating MAPK8IP1P2 reduced, while silencing MAPK8IP1P2 increased the luciferase reporter activity of HOP-Flash, but not the HIP-Flash ( Figure 5B ), suggesting that upregulating MAPK8IP1P2 inhibits the TEAD-dependent luciferase activity in thyroid cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, anoikis resistance was reported to be significantly correlated with positive lymph node metastasis in various cancers (12)(13)(14)(15)(16)(17). In this scenario, multiple signaling pathways have been demonstrate to promote anoikis resistance, including TGF-b, PI3K/AKT, and Hippo signaling, where the role of Hippo signaling in inducing anoikis resistance gains more attention (9,50,51). Importantly, inactivation of Hippo signaling has also been reported to promote lymphatic metastasis of cancers (52,53).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Ziyi Wang et al reported that EVA1A could inhibit NLRP3 activation to reduce liver hypoxia-reperfusion damage via inducing autophagy in Kupffer cells (29). On the other hand, Bang-Yi Lin et al found that EVA1A promoted papillary thyroid cancer progression and EMT by the Hippo signaling pathway (30). As a core kinase of the Hippo signaling pathway in cancers, MST1/2 participates in the development and function of Treg and Th17 cells (31).…”
Section: Discussionmentioning
confidence: 99%